Pre-Exposure Prophylaxis in a Reproductive Health Setting: A Quality Improvement Project. Issue 5 (September 2020) - Horack, Carrie L.; Newton, Sara L.; Vos, Michelle; Wolfe, Brenda A.; Whitaker, Amy
Introduction. Although pre-exposure prophylaxis (PrEP) is recommended by the Centers for Disease Control and Prevention, there is a practice gap in treatment at Planned Parenthood of Illinois. This project evaluated a clinical practice alert and evidence-based patient education script to determine if the intervention increased the number of appointments to discuss or initiate PrEP in patients at risk for acquiring HIV. Method. From October to December 2018, a clinical practice alert and evidence-based patient education script were implemented at one Planned Parenthood of Illinois health center. Aggregate data collected included the number of times the clinical alert was generated, the number of times staff read the script, the number of scheduled appointments to discuss PrEP, and the number of times PrEP was prescribed. Qualitative data were collected from clinic staff to further evaluate the intervention. Results. Eleven patients triggered the alert and staff read the education script nine times during the 8-week implementation period. One patient scheduled an appointment to discuss PrEP; no new prescriptions were initiated. One identified patient scheduled an appointment with a provider to initiate PrEP on a date after the implementation period ended. Staff found the alert and script helpful to initiate conversations with patients. Conclusions. This intervention established a system for clinic staff to identify patients at risk for acquiring HIV in order to discuss accurate, evidence-based PrEP information. Findings are limited to this particular setting due to a small sample size, which eliminated the possibility for statistical analysis.